Digital Microdroplet Ejection Technology-Based Heterogeneous Objects Prototyping - Na Li; Jiquan Yang; Chunmei Feng; Jianfei Yang; Liya Zhu; Aiqing Guo (International Journal of Biomedical Imaging)
An integrate fabrication framework is presented to build heterogeneous objects (HEO) using digital microdroplets injecting technology and rapid prototyping. The heterogeneous materials part design and manufacturing method in structure and material was used to change the traditional process. The net node method was used for digital modeling that can configure multimaterials in time. The relationship of material, color, and jetting nozzle was built. The main important contributions are to combine the structure, material, and visualization in one process and give the digital model for manufacture. From the given model, it is concluded that the method is effective for HEO. Using microdroplet rapid prototyping and the model given in the paper HEO could be gotten basically. The model could be used in 3D biomanufacturing.